2014
DOI: 10.1536/ihj.14-010
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends in Surgical Revascularization of Multivessel Coronary Artery Disease With Arterial Grafts

Abstract: SummaryIt is well known that graft patency determines prognosis in coronary artery bypass grafting. Numerous reports over the past 20 years have documented superior patency and prognosis when multiple arterial grafts are used. The use of the left internal thoracic artery to graft the left anterior descending artery has been widely accepted as the gold standard for surgical treatment of coronary disease for over 40 years. A considerable body of evidence suggests that the right internal thoracic artery behaves i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Evidence has shown that the use of composite Y/T grafts to avoid any manipulation of the diseased ascending aorta results in a low stroke rate. Although OPCAB with total arterial revascularization has been proposed as the gold standard approach to reduce neurocognitive dysfunction only for patients with severe atherosclerosis, 10,22) this no-touch procedure may not be routinely applied, particularly in emergent cases. Left ITA to Y graft anastomosis is more technically demanding than that of the ascending aorta and can result in a potential steal phenomenon of the left ITA by the anastomosed graft because most of the coronary circulation is supplied through a single inflow from the left ITA.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that the use of composite Y/T grafts to avoid any manipulation of the diseased ascending aorta results in a low stroke rate. Although OPCAB with total arterial revascularization has been proposed as the gold standard approach to reduce neurocognitive dysfunction only for patients with severe atherosclerosis, 10,22) this no-touch procedure may not be routinely applied, particularly in emergent cases. Left ITA to Y graft anastomosis is more technically demanding than that of the ascending aorta and can result in a potential steal phenomenon of the left ITA by the anastomosed graft because most of the coronary circulation is supplied through a single inflow from the left ITA.…”
Section: Discussionmentioning
confidence: 99%
“…When anastomosed to the left anteri-Vol 56 No 3 LITA GRAFT DISSECTION ASSESSED BY OCT AND IVUS or descending artery, LITA grafts are very favorable over a 10-year period. 1,2) The most common site of stenosis in the LITA graft is the distal anastomosis. 4) On the other hand, graft failure of LITA itself is rare but can occur.…”
Section: Discussionmentioning
confidence: 99%
“…1,2) The characteristics of the LITA including its elastomuscular composition and its well-known resistance to atherosclerosis are thought mainly to account for these favorable results.…”
mentioning
confidence: 99%
“…Another 14 patients died within 13 months to five years following surgery, and the causes of death included myocardial infarction (2), heart failure (3), infection (4), hepatic failure (1), gastrointestinal hemorrhage (1) and malignant tumor (3). Over five years after surgery, 25 patients died; the main causes of death were listed as follows: myocardial infarction (3), heart failure (4), cerebral hemorrhage (2), gastrointestinal hemorrhage (1), infection (5), renal failure (1), malignant tumor (6), high falling injury (1) and traffic accident (2). Additionally, 16 patients underwent repeat revascularization, with the incidence of 5.4%.…”
Section: Study Populationmentioning
confidence: 99%
“…1) Afterwards, RA graft re-patency following early vasospasm and functional occlusion was found, wakening cardiac surgeons' interest in the RA grafting. 2) Subsequently, the use of the RA as a bypass conduit for CABG was increasing.…”
mentioning
confidence: 99%